Female Leadership and Social Networks: Are Female University Professors Digital References for their Female Students? - Rodríguez Fernández, Leticia; Macías-Varela, Belén; Simancas-González, Esther (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Women's leadership is a pending task in the university environment, where few women manage to reach the highest management positions or professorships. This paper considers whether this lack of visibility also occurs in social networks, a highly relevant showcase for students who spend a large part of their time in these environments. We present a mixed research, with quantitative surveys to both faculty (n=250) and students (n=990) of the University of Cadiz (UCA) and structured interviews (n=10) to an equal sample of male and female deans.